Farm layout and planting system for sweetpotato production in Malaysia. - Ahmad, Desa; Hamid, Akhir; Rukunnuddin, Ibni Hajar (Farm Machinery Industrial Research Corp., 2012)
This paper looks at the needs and potential for mechanized operations in the production of sweetpotatoes in Malaysia, focusing on landscape planning to suit the field machinery used. It briefly explains the planning considerations and the availability of machines for these operations. Almost all field operations in the production of sweetpotatoes on mineral and problem soils, except peat soil, can be mechanized; however, a few operations may still need to be done manually. The scale of production determines the extent of mechanization to be adopted. Careful planning is required because mechanized production involves a large amount of capital. Planning should involve establishing a suitable schedule to carry out field operations and selecting the appropriate machines. Local environmental and topographical factors at the farm also need to be considered in the planning of mechanized sweetpotato production.